2020
DOI: 10.1155/2020/1026240
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis, Independent of Uric Acid, Increased Risk of Coronary Artery and Carotid Atherosclerosis: A Meta‐Analysis of Observational Studies

Abstract: Background and Aims. Recent epidemiological evidence indicates an association between urolithiasis and atherosclerosis; however, results are incongruous. Our aim is to summarize the association between urolithiasis and arteriosclerosis risk through a detailed meta-analysis. Methods. Relevant studies published before April 2019 were identified by searching OVID, EMBASE, PubMed, Web of Science database, and Cochrane Library. The relationship between urolithiasis and the risk of atherosclerosis was assessed by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…Прежде чем эти общие патофизиологические механизмы и факторы риска реализуются в ИБС и инсульт, должен наблюдаться повышенный риск атеросклеротического поражения артерий у больных МКБ. Такие исследования есть -они обобщены в мета-анализе W. Luo и соавт., и подтверждают, что МКБ связана с повышенным риском атеросклероза, особенно коронарных и каротидных артерий [54]. Для коронарного атеросклероза ОШ=1,59, (95% ДИ=1,44-1,75), для каротидного атеросклероза ОШ=1,68, (95% ДИ=1, 29).…”
Section: гипотезы общих факторов риска мкб и ссзunclassified
See 1 more Smart Citation
“…Прежде чем эти общие патофизиологические механизмы и факторы риска реализуются в ИБС и инсульт, должен наблюдаться повышенный риск атеросклеротического поражения артерий у больных МКБ. Такие исследования есть -они обобщены в мета-анализе W. Luo и соавт., и подтверждают, что МКБ связана с повышенным риском атеросклероза, особенно коронарных и каротидных артерий [54]. Для коронарного атеросклероза ОШ=1,59, (95% ДИ=1,44-1,75), для каротидного атеросклероза ОШ=1,68, (95% ДИ=1, 29).…”
Section: гипотезы общих факторов риска мкб и ссзunclassified
“…Примечательно, что риск атеросклероза у больных МКБ не зависел от уровня мочевой кислоты, а также от уровня дислипидемии и артериального давления. Авторы мета-анализа делают вывод, что МКБ может быть независимым фактором риска атеросклероза [54].…”
Section: гипотезы общих факторов риска мкб и ссзunclassified
“…Even though kidney stones are not fatal, they may provoke cardiovascular diseases that are among the diseases with the highest mortality rates [72,73]. Several studies investigated the association between urolithiasis/nephrolithiasis and cardiovascular diseases including atherosclerotic plaques [72][73][74][75][76][77][78]. Aydin et al investigated data from two hundred patients with kidney stones composed of calcium oxalate and two hundred controls to estimate the ten-year risk of cardiovascular disease and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of all the studies' results revealed that the possibility of atherosclerotic plaque formation when ureteric stones were found in the samples was higher [79]. Although the association between ureteric/kidney stones and atherosclerotic plaques requires more investigation, the screening for cardiovascular diseases in patients with ureteric/kidney stones shall be taken into consideration [77,78].…”
Section: Introductionmentioning
confidence: 99%